Removal and attenuation of sewage effluent combined tracer signals of phosphorus, caffeine and saccharin in soil. (April 2017) - Richards, Samia; Withers, Paul J.A.; Paterson, Eric; McRoberts, Colin W.; Stutter, Marc
Abstract: Contaminants in septic tank effluent (STE) are expected to be removed by the soil system before discharging to the environment. However, potential contaminants such as phosphorus (P), caffeine and artificial sweeteners do find their way to watercourses impacting aquatic eco systems. In this study, the attenuation of STE P, caffeine and saccharin were investigated in untreated soil and in soil with reduced microbial activity, in aqueous solutions and in the complex matrix of STE. Time series sorption and desorption experiments using batch equilibrium and a column experiment of STE P attenuation were conducted. The results revealed that the soil distribution coefficients ( K d ) were: P 81.57 > caffeine 22.16 > saccharin 5.98 cm 3 /g, suggesting greater soil affinity to P adsorption. The data revealed that 80% of saccharin and 33% of caffeine attenuation was associated with microbial activities rather than adsorption processes. However, a complete removal of saccharin and caffeine did not occur during the equilibration period, suggesting their leaching potential. The dominant mechanism of P attenuation was adsorption (chemical and physical), yielding P retention of >73% and 35% for P in aqueous solution and in STE matrix, respectively, for batch equilibrium. The soil in the column acted as effluent P sink retaining 125 μg P/g soil of effluent P. The attenuation of P, caffeine and saccharin in the aqueous solution was greater than in STE, suggesting that the complex composition of STE reduced soil adsorption ability, and that other substances present in STE may be competing for soil binding sites. The data revealed that caffeine and P had similarities in the interaction with soils and thus caffeine may be considered as a STE tracer of anthropogenic source of P in receiving waters. Graphical abstract: Highlights: Sorption distribution coefficient K d : phosphorus (P)> caffeine > saccharin. Caffeine, saccharin and P's sorption in STE differed from that in aqueous solutions. The complex composition of STE reduced sorption ability of the tested substances. Phosphorus and caffeine had similar attenuation behaviour in the test soil. Phosphorus had the greatest desorption and leaching ability followed by caffeine. Abstract : Septic tank effluent behaved differently on contact with soil relative to aqueous solution. Less Phosphorus was removed from septic tank effluent by the soil as the complex composition of STE may have competed for soil adsorption sites.